The Effectiveness of Learning Basic Concepts of Art for Primary Teacher Education Students Using Nomor Acak Learning Model - Zufriady, Zufriady; Kurniaman, Otang (Universitas Pendidikan Indonesia, 2019)
The nomor acak learning model is done by randomly giving number to each student and making them remember it from the beginning to the end of the lecture. The function was to make each student be more active in the teaching and learning activities, since they must be prepared with their respective material if the number was called. This research employed a quasi-experimental research method with one group pre-test/post-test design. The determinant coefﬁcient data of the effect of nomor acak models on the effectiveness of primary teacher education students obtained a class A data of 58.21%, class B of 36% and class C of 23%. This research was conducted at the primary teacher education program for six months in the Basic Concepts of Art courses to students of 2018. It could be concluded that the nomor acak learning model could improve the learning outcomes of students of the primary teacher education program in the Basic Concepts of Art course.